Micro-nano fiber material as well as preparation method and application thereof

By using micro-nano fiber materials in disposable medical or sanitary PP non-woven fabrics, and using a combination of degradable matrix and composite antibacterial agents, the problem of lack of antibacterial function and non-degradability of traditional non-woven fabrics is solved, and long-lasting antibacterial, Good breathability and biodegradability.

CN119308030APending Publication Date: 2025-01-14GUANGDONG VOCATIONAL & TECHNICAL COLLEGE
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411486190.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Traditional disposable medical or sanitary PP non-woven fabrics have problems such as lack of antibacterial functions, insecure disinfection methods, poor breathability, and non-degradability during manufacturing and use, resulting in short service life, insufficient safety and environmental protection.

Method used

Micro-nano fiber material is used, and its preparation raw materials include a degradable matrix and a composite antibacterial agent. The composite antibacterial agent is made from polyvinyl alcohol and a polymer antibacterial agent through a cross-linking reaction to ensure good compatibility and long-term stability between the antibacterial agent and the degradable matrix. stability.

Benefits of technology

It achieves the long-lasting antibacterial function of micro-nano fiber materials, good air permeability, no migration and accumulation of antibacterial agents and toxic side effects. The material is completely biodegradable and avoids environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119308030A_ABST
    Figure CN119308030A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of antibacterial materials, and discloses a micro-nano fiber material as well as a preparation method and application thereof. The preparation raw materials of the micro-nano fiber material comprise a degradable matrix and a composite antibacterial agent, the preparation raw materials of the composite antibacterial agent comprise polyvinyl alcohol and a high-molecular antibacterial agent, and the high-molecular antibacterial agent is a ternary copolymerized quaternary ammonium salt high-molecular antibacterial agent with the publication number of CN117304390A. The polyvinyl alcohol is introduced into the composite antibacterial agent, so that the compatibility of the composite antibacterial agent and a degradable matrix in the subsequent spinning forming processing and using process is further improved, the dispersion uniformity and long-term stability of a macromolecular antibacterial agent in the degradable matrix can be further improved, migration and enrichment are avoided, and toxic and side effects are avoided; and the micro-nano fiber material has a lasting antibacterial function, is biodegradable and has good air permeability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of antibacterial materials, and particularly relates to a micro-nano fiber material and a preparation method and application thereof. Background Art

[0002] Traditional disposable medical or sanitary PP nonwovens have many technical defects in the manufacturing and use process:

[0003] (1) Disposable medical or sanitary products made of PP non-woven fabrics need to be sterilized by radiation or fumigation with carcinogenic ethylene oxide. If gamma radiation or high-energy electron beam radiation is used for sterilization, its efficacy will be reduced and the manufacturing cost will be increased. If ethylene oxide is used for sterilization, not only will the sterilization efficiency be low, but the residual ethylene oxide will also pose a potential carcinogenic risk and environmental pollution.

[0004] (2) Disposable medical or sanitary products made of traditional PP non-woven fabrics do not have antibacterial properties and are prone to breed bacteria during use, resulting in a very short continuous use time.

[0005] (3) Traditional antimicrobial agents cannot be used in protective or insulating materials such as PP nonwoven fabrics, mainly for the following reasons: 1. Traditional inorganic antimicrobial agents such as metallic silver and copper compounds added to PP materials result in poor compatibility and decreased mechanical properties. Moreover, long-term use will lead to the migration and accumulation of metal ions, thus causing toxic side effects on the human body. 2. Conventional broad-spectrum antimicrobial agents such as small molecule quaternary ammonium salts and small molecule guanidine salts have broad-spectrum antimicrobial activity, but these small molecule antimicrobial agents are easily soluble in water and may migrate and be lost during use.

[0006] (4) PP multi-layer composite non-woven fabric products have poor air permeability. During the wearing process, the condensation of water vapor in the exhaled gas will cause the pores in the PP disposable non-woven fabric to be blocked, further deteriorating the air permeability of the PP non-woven fabric product and causing the wearer's comfort to further decrease. Long-term wearing can also easily cause skin whitening, swelling, and even eczema and other discomfort symptoms.

[0007] (5) Disposable medical or sanitary products are used in large quantities, but most of them use non-degradable PP as raw material. After use and disposal, they are generally incinerated or landfilled as waste, which will cause pollution and harm to the environment.

[0008] There are several main solutions for achieving the antibacterial function of degradable antibacterial fiber materials. A few are directly made of natural fibers with certain antibacterial functions, such as bamboo fiber and chitosan fiber. Bamboo fiber has limited antibacterial function and insufficient antibacterial efficiency, while the raw material source of chitosan fiber is limited and the cost is high. Therefore, only a small number of products are currently used on the market, which is difficult to meet the market's popularization and application needs. In addition, most of them achieve antibacterial function by adding antibacterial additives to degradable raw materials. There are mainly two types of antibacterial agents: ① Adding metal ions or metal oxides, such as nano zinc oxide, nano silver, nano titanium dioxide, etc.; ② Adding organic synthetic antibacterial agents or natural organic product antibacterial ingredients, such as sulfadiazine zinc, chitosan, etc. The antibacterial function is obtained by adding antibacterial agents to the raw materials before spinning, or by first spinning and then adsorbing them on the fiber surface through solution impregnation or coating. The degradable antibacterial fibers prepared by these technical solutions either have the problem of metal ion migration and enrichment, or the instability of antibacterial agents such as the migration and enrichment of organic synthetic small molecules or naturally extracted small molecules, making it difficult to achieve the requirements of long-term stability of antibacterial function, safety of use, low cost and large-scale application. Summary of the invention

[0009] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a micro-nano fiber material and a preparation method and application thereof, wherein the micro-nano fiber material itself has a durable antibacterial function and is biodegradable, has good air permeability, and has no antibacterial agent migration and enrichment, and has no toxic side effects.

[0010] The first aspect of the present invention provides a micro-nano fiber material, wherein the raw materials for preparing the micro-nano fiber material include a degradable matrix and a composite antibacterial agent, the raw materials for preparing the composite antibacterial agent include polyvinyl alcohol and a polymer antibacterial agent, and the polymer antibacterial agent is a ternary copolymer quaternary ammonium salt polymer antibacterial agent disclosed in CN117304390A.

[0011] In some embodiments of the present invention, the polymer antibacterial agent is named as Compolyamonia; the composite antibacterial agent is named as Compolyamonia-PVA, and its structural formula is as follows:

[0012] In the structural formula Represents a polymer chain that is continuously extended.

[0013] In some embodiments of the present invention, the mass ratio of the degradable matrix to the composite antibacterial agent is 98:2 to 50:50.

[0014] In some embodiments of the present invention, the mass ratio of the degradable matrix to the composite antibacterial agent is 95:5 to 50:50.

[0015] In some embodiments of the present invention, the mass ratio of the degradable matrix to the composite antibacterial agent is 95:5 to 12.5:87.5.

[0016] In some embodiments of the present invention, the degradable matrix includes at least one of polylactic acid PLA, polyvinyl alcohol PVA, polycaprolactone PCL, polybutylene succinate PBS, polybutylene terephthalate and polybutylene adipate copolymer PBAT, polypropylene carbonate PPC, polyester-polypropylene carbonate copolymer PPC-P, polyhydroxyalkanoate PHA, lignin, plant cellulose, cotton, linen, and silk.

[0017] In some embodiments of the present invention, the alcoholysis degree of the polyvinyl alcohol is 30% to 95%; and / or the number average molecular weight of the polyvinyl alcohol is 5000 to 120000; and / or the molecular weight distribution width of the polyvinyl alcohol is 2 to 4; and / or the average degree of polymerization of the polyvinyl alcohol is 100 to 2500.

[0018] In some embodiments of the present invention, the number average molecular weight of the polymer antibacterial agent is 2000 to 100000; and / or the molecular weight distribution width of the polymer antibacterial agent is 1 to 4; and / or the molar ratio of N,N-dimethyl-N-allyldodecylammonium bromide to vinyltri(methoxy)silane in the molecular backbone of the polymer antibacterial agent is 3:7 to 9:1.

[0019] In some embodiments of the present invention, the mass ratio of the polymer antibacterial agent to polyvinyl alcohol is 10:0.1 to 1:9.

[0020] In some embodiments of the present invention, the mass ratio of the polymer antibacterial agent to polyvinyl alcohol is 7:3 to 1:9.

[0021] In some embodiments of the present invention, the composite antibacterial agent is mainly prepared by cross-linking reaction of polyvinyl alcohol and a polymer antibacterial agent.

[0022] In some embodiments of the present invention, the degradable matrix also includes an auxiliary resin, and the auxiliary resin includes at least one of polyethylene terephthalate PET, polybutylene terephthalate PBT, polypropylene terephthalate PTT, polyethylene terephthalate and polycyclohexane terephthalate copolymer PETG, polycaprolactam PA6, polyheptanolactam PA7, polycapryllactam PA8, and polyhexamethylene adipate PA66.

[0023] In some embodiments of the present invention, the mass of the auxiliary resin accounts for 0.1% to 30% of the mass of the degradable matrix.

[0024] In some embodiments of the present invention, the degradable matrix further comprises a nano inorganic filler, and the nano inorganic filler comprises at least one of nano silicon dioxide, nano titanium dioxide, nano hydrotalcite, nano tourmaline (or negative ion powders such as vermiculite), and nano mica powder.

[0025] In some embodiments of the present invention, the particle size distribution of the nano inorganic filler is 5 to 100 nm.

[0026] In some embodiments of the present invention, the average diameter of the fibers in the micro-nano fiber material is 20 nm to 10 μm.

[0027] In some embodiments of the present invention, the average diameter of the fibers in the micro-nano fiber material is 100 nm to 2000 nm.

[0028] In some embodiments of the present invention, the average diameter of the fibers in the micro-nano fiber material is 100 nm to 500 nm.

[0029] The second aspect of the present invention provides a method for preparing the micro-nano fiber material according to the first aspect of the present invention, comprising the following steps:

[0030] The polyvinyl alcohol and the high molecular antibacterial agent are mixed and cross-linked to obtain the composite antibacterial agent;

[0031] The degradable matrix and the composite antibacterial agent are mixed and spun to obtain the micro-nano fiber material.

[0032] In some embodiments of the present invention, the temperature of the cross-linking reaction is 70 to 200° C.; and / or the time of the cross-linking reaction is 60 s to 10 h.

[0033] In some embodiments of the present invention, the spinning is performed by melt-blowing, melt electrospinning or solution electrospinning.

[0034] In some embodiments of the present invention, the process conditions of the melt-blowing spinning are: temperature 150° C. to 260° C., and screw speed 10 to 200 rpm.

[0035] In some embodiments of the present invention, the process conditions of the melt electrospinning are: temperature 50°C to 185°C, screw speed 2 to 70 rpm, spinning voltage 20 to 60 kV, distance between spinneret and electrode plate 5 to 20 cm, and collection roller speed 1200 to 2500 rpm.

[0036] In some embodiments of the present invention, the process conditions of the solution electrospinning are: the mass concentration of the spinning solution is 2% to 20%, the spinning voltage is 5 to 50 kV, the solution flow rate is 0.2 to 10 mL / min, the distance between the collecting roller and the electrode is 10 to 25 cm, and the rotation speed of the collecting roller is 800 to 1500 rpm.

[0037] In some embodiments of the present invention, the specific preparation process of the composite antibacterial agent is as follows: the polyvinyl alcohol and the polymer antibacterial agent are solution blended or melt blended, and at the same time, under continuous stirring (solution blending) or screw shearing (melt blending), the reaction is kept at 70-200°C for a certain period of time (the higher the temperature, the shorter the time required for the cross-linking reaction, and the reaction time is 60s to 10h). After the two are fully cross-linked, a composite antibacterial agent Compolyamonia-PVA in which Copolyamonia is cross-linked on the main chain of the polyvinyl alcohol molecule by chemical bonds is prepared.

[0038] Specifically, the principle of the cross-linking reaction is as follows:

[0039]

[0040] The third aspect of the present invention provides an application of the micro-nano fiber material described in the first aspect of the present invention, and the application includes the application of the micro-nano fiber material in the preparation of disposable sanitary products, disposable protective products, Band-Aids, medical bandages, and filtration and purification products.

[0041] Specifically, the disposable sanitary products include baby diapers, sanitary napkins, disposable medical sanitary pads, and medical protective clothing; the disposable protective products include medical surgical masks and protective masks; the filtration and purification products include air filters and water purification filters.

[0042] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0043] (1) The micro-nano fiber material of the present invention, by introducing polyvinyl alcohol into the composite antibacterial agent, can further improve the compatibility of the composite antibacterial agent with the degradable matrix during the subsequent spinning molding process and use, and can further improve the dispersion uniformity and long-term stability of the polymer antibacterial agent in the degradable matrix, without migration and enrichment, no toxic side effects, no environmental pollution, and can avoid the technical defects of traditional inorganic metal antibacterial agents and small molecule organic antibacterial agents.

[0044] (2) The present invention regulates the dosage of the matrix and the composite antibacterial agent so that the micro-nano fiber material itself has a long-lasting antibacterial function, with an antibacterial rate of more than 99%. The antibacterial rate can still reach more than 90% after continuous use for 7 days. No radiation or fumigation disinfection process is required. After being produced in a clean environment, it can be directly applied to the fields of hygiene, medical treatment, protection, and filtration.

[0045] (3) The micro-nano fiber material of the present invention is completely biodegradable, has no residual environmental pollution, and can avoid the technical disadvantages of traditional non-woven fabrics that they are non-degradable. The composting degradation period is ≤ 180 days (under composting conditions of 60° C. and 50% relative humidity, 100% degradation within 180 days).

[0046] (4) The micro-nano fiber material of the present invention has a small average diameter, and the filtration efficiency of particles with an average particle size of 0.3 μm can reach more than 99%. It has high filtration efficiency, good protection effect, and excellent air permeability. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 This is a physical picture of the micro-nano fiber membrane prepared in Example 5 of the present invention;

[0048] Figure 2 This is a SEM image of the micro-nano fiber membrane prepared in Example 5 of the present invention;

[0049] Figure 3 A comparison chart of the antibacterial test of the micro-nano fiber membranes prepared in different embodiments of the present invention against different bacterial species;

[0050] Figure 4 The figure is a comparison chart of the antibacterial properties of mask samples made using the micro-nano fiber membrane of Example 5 of the present invention and a commercially available antibacterial melt-blown non-woven fabric after being used for different periods of time. DETAILED DESCRIPTION

[0051] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.

[0052] Unless otherwise specified, the raw materials, reagents or devices used in the present invention can be obtained from conventional commercial channels or by existing known methods.

[0053] In the technical scheme of the present invention, no matter which spinning process is used, as long as the degradable matrix is ​​the same and the content of the composite antibacterial agent is the same, the various properties of the prepared micro-nano fibers are close or similar, with only slight differences in production efficiency and fiber diameter. Therefore, the following mainly takes solution electrospinning (Examples 1-15) and melt electrospinning (Example 16) as examples to illustrate the implementation process of the present invention.

[0054] The composite antibacterial agent Compolyamonia-PVA in the embodiment of the present invention is prepared by the following steps:

[0055] (1) Weigh 0.06 mol of N,N-dimethyl-N-allyl dodecyl ammonium bromide and 0.04 mol of vinyl tri(methoxy)silane, weigh azobisisobutyronitrile (AIBN) as a polymerization initiator according to 0.15% of the total mass of the reactants, and add an appropriate amount of anhydrous ethanol as a solvent. Under nitrogen protection, react at 60° C. in a reactor for 20 hours, and then stop the reaction to obtain a polymer antibacterial agent (named Copolyamonia);

[0056] (2) Copolyamonia and polyvinyl alcohol were mixed in a solution at a mass ratio of 7:3, and the mixture was kept at 160°C for 4 hours under continuous stirring to allow the two to fully cross-link and prepare a composite antibacterial agent (named Compolyamonia-PVA) in which Copolyamonia was cross-linked on the main chain of the polyvinyl alcohol molecule through chemical bonds.

[0057] Example 1

[0058] A micro-nano fiber membrane is prepared by the following steps:

[0059] (1) weighing a degradable matrix raw material according to a mass ratio of PLA / PPC-P=6:4, weighing Compolyamonia-PVA according to a mass ratio of Compolyamonia-PVA / (PLA+PPC-P)=5:95, then adding the degradable matrix raw material and Compolyamonia-PVA simultaneously into an appropriate amount of dimethyl sulfoxide solvent, stirring and dissolving at room temperature, preparing a spinning solution with a mass concentration of the degradable matrix raw material of 5wt%, and then filtering and standing for degassing;

[0060] (2) Turn on the electrospinning machine and set the spinning conditions: spinning voltage 30 kV, solution flow rate 1 mL / h, collection roller speed 800 rpm, and a distance of 15 cm between the collection roller and the electrode; first cover the collection roller with a collection substrate layer, then start the collection roller, then start the spinning solution pump switch, and finally connect the high voltage power supply to the spinning electrode to start spinning;

[0061] (3) When the spinning time reaches 45 minutes, turn off the spinning solution delivery pump, the collecting roller, and the spinning power supply, and then peel off the micro-nano fiber membrane from the collecting roller substrate layer.

[0062] Example 2

[0063] A micro-nano fiber membrane is prepared by the following steps:

[0064] (1) weighing a degradable matrix raw material according to a mass ratio of PLA / PPC-P=6:4, weighing Compolyamonia-PVA according to a mass ratio of Compolyamonia-PVA / (PLA+PPC-P)=5:95, then adding the degradable matrix raw material and Compolyamonia-PVA simultaneously into an appropriate amount of dimethyl sulfoxide solvent, stirring and dissolving at room temperature, preparing a spinning solution with a mass concentration of the degradable matrix raw material of 7wt%, and then filtering and standing for degassing;

[0065] (2) Turn on the electrospinning machine and set the spinning conditions: spinning voltage 30 kV, solution flow rate 1 mL / h, collection roller speed 800 rpm, and a distance of 15 cm between the collection roller and the electrode; first cover the collection roller with a collection substrate layer, then start the collection roller, then start the spinning solution pump switch, and finally connect the high voltage power supply to the spinning electrode to start spinning;

[0066] (3) When the spinning time reaches 45 minutes, turn off the spinning solution delivery pump, the collecting roller, and the spinning power supply, and then peel off the micro-nano fiber membrane from the collecting roller substrate layer.

[0067] Example 3

[0068] A micro-nano fiber membrane is prepared by the following steps:

[0069] (1) weighing a degradable matrix raw material according to a mass ratio of PLA / PPC-P=6:4, weighing Compolyamonia-PVA according to a mass ratio of Compolyamonia-PVA / (PLA+PPC-P)=5:95, then adding the degradable matrix raw material and Compolyamonia-PVA simultaneously into an appropriate amount of dimethyl sulfoxide solvent, stirring and dissolving at room temperature, preparing a spinning solution with a mass concentration of the degradable matrix raw material of 10wt%, and then filtering and standing for degassing;

[0070] (2) Turn on the electrospinning machine and set the spinning conditions: spinning voltage 30 kV, solution flow rate 1 mL / h, collection roller speed 800 rpm, and a distance of 15 cm between the collection roller and the electrode; first cover the collection roller with a collection substrate layer, then start the collection roller, then start the spinning solution pump switch, and finally connect the high voltage power supply to the spinning electrode to start spinning;

[0071] (3) When the spinning time reaches 45 minutes, turn off the spinning solution delivery pump, the collecting roller, and the spinning power supply, and then peel off the micro-nano fiber membrane from the collecting roller substrate layer.

[0072] Example 4

[0073] A micro-nano fiber membrane is prepared by the following steps:

[0074] (1) weighing a degradable matrix raw material according to a mass ratio of PLA / PPC-P=6:4, weighing Compolyamonia-PVA according to a mass ratio of Compolyamonia-PVA / (PLA+PPC-P)=5:95, then adding the degradable matrix raw material and Compolyamonia-PVA simultaneously into an appropriate amount of dimethyl sulfoxide solvent, stirring and dissolving at room temperature, preparing a spinning solution with a mass concentration of the degradable matrix raw material of 12wt%, and then filtering and standing for degassing;

[0075] (2) Turn on the electrospinning machine and set the spinning conditions: spinning voltage 30 kV, solution flow rate 1 mL / h, collection roller speed 800 rpm, and a distance of 15 cm between the collection roller and the electrode; first cover the collection roller with a collection substrate layer, then start the collection roller, then start the spinning solution pump switch, and finally connect the high voltage power supply to the spinning electrode to start spinning;

[0076] (3) When the spinning time reaches 45 minutes, turn off the spinning solution delivery pump, the collecting roller, and the spinning power supply, and then peel off the micro-nano fiber membrane from the collecting roller substrate layer.

[0077] Example 5

[0078] A micro-nano fiber membrane is prepared by the following steps:

[0079] (1) weighing a degradable matrix raw material according to a mass ratio of PLA / PPC-P=6:4, weighing Compolyamonia-PVA according to a mass ratio of Compolyamonia-PVA / (PLA+PPC-P)=5:95, then adding the degradable matrix raw material and Compolyamonia-PVA simultaneously into an appropriate amount of dimethyl sulfoxide solvent, stirring and dissolving at room temperature, preparing a spinning solution with a mass concentration of the degradable matrix raw material of 15wt%, and then filtering and standing for degassing;

[0080] (2) Turn on the electrospinning machine and set the spinning conditions: spinning voltage 30 kV, solution flow rate 1 mL / h, collection roller speed 800 rpm, and a distance of 15 cm between the collection roller and the electrode; first cover the collection roller with a collection substrate layer, then start the collection roller, then start the spinning solution pump switch, and finally connect the high voltage power supply to the spinning electrode to start spinning;

[0081] (3) When the spinning time reaches 45 minutes, turn off the spinning solution delivery pump, the collecting roller, and the spinning power supply, and then peel off the micro-nano fiber membrane from the collecting roller substrate layer.

[0082] Example 6

[0083] A micro-nano fiber membrane is prepared by the following steps:

[0084] (1) weighing a degradable matrix raw material according to a mass ratio of PLA / PPC-P=6:4, weighing Compolyamonia-PVA according to a mass ratio of Compolyamonia-PVA / (PLA+PPC-P)=2.5:97.5, then adding the degradable matrix raw material and Compolyamonia-PVA simultaneously into an appropriate amount of dimethyl sulfoxide solvent, stirring and dissolving at room temperature, preparing a spinning solution with a mass concentration of the degradable matrix raw material of 5wt%, and then filtering and standing for degassing;

[0085] (2) Turn on the electrospinning machine and set the spinning conditions: spinning voltage 30 kV, solution flow rate 1 mL / h, collection roller speed 800 rpm, and a distance of 15 cm between the collection roller and the electrode; first cover the collection roller with a collection substrate layer, then start the collection roller, then start the spinning solution pump switch, and finally connect the high voltage power supply to the spinning electrode to start spinning;

[0086] (3) When the spinning time reaches 45 minutes, turn off the spinning solution delivery pump, the collecting roller, and the spinning power supply, and then peel off the micro-nano fiber membrane from the collecting roller substrate layer.

[0087] Example 7

[0088] A micro-nano fiber membrane is prepared by the following steps:

[0089] (1) weighing a degradable matrix raw material according to a mass ratio of PLA / PPC-P=6:4, weighing Compolyamonia-PVA according to a mass ratio of Compolyamonia-PVA / (PLA+PPC-P)=7.5:92.5, then adding the degradable matrix raw material and Compolyamonia-PVA simultaneously into an appropriate amount of dimethyl sulfoxide solvent, stirring and dissolving at room temperature, preparing a spinning solution with a mass concentration of the degradable matrix raw material of 5wt%, and then filtering and standing for degassing;

[0090] (2) Turn on the electrospinning machine and set the spinning conditions: spinning voltage 30 kV, solution flow rate 1 mL / h, collection roller speed 800 rpm, and a distance of 15 cm between the collection roller and the electrode; first cover the collection roller with a collection substrate layer, then start the collection roller, then start the spinning solution pump switch, and finally connect the high voltage power supply to the spinning electrode to start spinning;

[0091] (3) When the spinning time reaches 45 minutes, turn off the spinning solution delivery pump, the collecting roller, and the spinning power supply, and then peel off the micro-nano fiber membrane from the collecting roller substrate layer.

[0092] Example 8

[0093] A micro-nano fiber membrane is prepared by the following steps:

[0094] (1) weighing a degradable matrix raw material according to a mass ratio of PLA / PPC-P=6:4, weighing Compolyamonia-PVA according to a mass ratio of Compolyamonia-PVA / (PLA+PPC-P)=10:90, then adding the degradable matrix raw material and Compolyamonia-PVA simultaneously into an appropriate amount of dimethyl sulfoxide solvent, stirring and dissolving at room temperature, preparing a spinning solution with a mass concentration of the degradable matrix raw material of 5wt%, and then filtering and standing for degassing;

[0095] (2) Turn on the electrospinning machine and set the spinning conditions: spinning voltage 30 kV, solution flow rate 1 mL / h, collection roller speed 800 rpm, and a distance of 15 cm between the collection roller and the electrode; first cover the collection roller with a collection substrate layer, then start the collection roller, then start the spinning solution pump switch, and finally connect the high voltage power supply to the spinning electrode to start spinning;

[0096] (3) When the spinning time reaches 45 minutes, turn off the spinning solution delivery pump, the collecting roller, and the spinning power supply, and then peel off the micro-nano fiber membrane from the collecting roller substrate layer.

[0097] Example 9

[0098] A micro-nano fiber membrane is prepared by the following steps:

[0099] (1) weighing the degradable matrix raw material according to the mass ratio of PLA / PPC-P=6:4, weighing Compolyamonia-PVA according to the mass ratio of Compolyamonia-PVA / (PLA+PPC-P)=12.5:87.5, then adding the degradable matrix raw material and Compolyamonia-PVA into an appropriate amount of dimethyl sulfoxide solvent at the same time, stirring and dissolving at room temperature, preparing a spinning solution with a mass concentration of the degradable matrix raw material of 5wt%, and then filtering and standing for degassing;

[0100] (2) Turn on the electrospinning machine and set the spinning conditions: spinning voltage 30 kV, solution flow rate 1 mL / h, collection roller speed 800 rpm, and a distance of 15 cm between the collection roller and the electrode; first cover the collection roller with a collection substrate layer, then start the collection roller, then start the spinning solution pump switch, and finally connect the high voltage power supply to the spinning electrode to start spinning;

[0101] (3) When the spinning time reaches 45 minutes, turn off the spinning solution delivery pump, the collecting roller, and the spinning power supply, and then peel off the micro-nano fiber membrane from the collecting roller substrate layer.

[0102] Example 10

[0103] A micro-nano fiber membrane is prepared by the following steps:

[0104] (1) weighing a degradable matrix raw material according to a mass ratio of PLA / PPC-P=6:4, weighing Compolyamonia-PVA according to a mass ratio of Compolyamonia-PVA / (PLA+PPC-P)=5:95, then adding the degradable matrix raw material and Compolyamonia-PVA simultaneously into an appropriate amount of dimethyl sulfoxide solvent, stirring and dissolving at room temperature, preparing a spinning solution with a mass concentration of the degradable matrix raw material of 5wt%, and then filtering and standing for degassing;

[0105] (2) Turn on the electrospinning machine and set the spinning conditions: spinning voltage 20 kV, solution flow rate 1 mL / h, collection roller speed 800 rpm, and a distance of 15 cm between the collection roller and the electrode; first cover the collection roller with a collection substrate layer, then start the collection roller, then start the spinning solution pump switch, and finally connect the high voltage power supply to the spinning electrode to start spinning;

[0106] (3) When the spinning time reaches 45 minutes, turn off the spinning solution delivery pump, the collecting roller, and the spinning power supply, and then peel off the micro-nano fiber membrane from the collecting roller substrate layer.

[0107] Embodiment 11

[0108] A micro-nano fiber membrane is prepared by the following steps:

[0109] (1) weighing a degradable matrix raw material according to a mass ratio of PLA / PPC-P=6:4, weighing Compolyamonia-PVA according to a mass ratio of Compolyamonia-PVA / (PLA+PPC-P)=5:95, then adding the degradable matrix raw material and Compolyamonia-PVA simultaneously into an appropriate amount of dimethyl sulfoxide solvent, stirring and dissolving at room temperature, preparing a spinning solution with a mass concentration of the degradable matrix raw material of 5wt%, and then filtering and standing for degassing;

[0110] (2) Turn on the electrospinning machine and set the spinning conditions: spinning voltage 25 kV, solution flow rate 1 mL / h, collection roller speed 800 rpm, and a distance of 15 cm between the collection roller and the electrode; first cover the collection roller with a collection substrate layer, then start the collection roller, then start the spinning solution pump switch, and finally connect the high voltage power supply to the spinning electrode to start spinning;

[0111] (3) When the spinning time reaches 45 minutes, turn off the spinning solution delivery pump, the collecting roller, and the spinning power supply, and then peel off the micro-nano fiber membrane from the collecting roller substrate layer.

[0112] Example 12

[0113] A micro-nano fiber membrane is prepared by the following steps:

[0114] (1) weighing a degradable matrix raw material according to a mass ratio of PLA / PPC-P=6:4, weighing Compolyamonia-PVA according to a mass ratio of Compolyamonia-PVA / (PLA+PPC-P)=5:95, then adding the degradable matrix raw material and Compolyamonia-PVA simultaneously into an appropriate amount of dimethyl sulfoxide solvent, stirring and dissolving at room temperature, preparing a spinning solution with a mass concentration of the degradable matrix raw material of 5wt%, and then filtering and standing for degassing;

[0115] (2) Turn on the electrospinning machine and set the spinning conditions: spinning voltage 35 kV, solution flow rate 1 mL / h, collection roller speed 800 rpm, and a distance of 15 cm between the collection roller and the electrode; first cover the collection roller with a collection substrate layer, then start the collection roller, then start the spinning solution pump switch, and finally connect the high voltage power supply to the spinning electrode to start spinning;

[0116] (3) When the spinning time reaches 45 minutes, turn off the spinning solution delivery pump, the collecting roller, and the spinning power supply, and then peel off the micro-nano fiber membrane from the collecting roller substrate layer.

[0117] Embodiment 13

[0118] A micro-nano fiber membrane is prepared by the following steps:

[0119] (1) weighing a degradable matrix raw material according to a mass ratio of PLA / PPC-P=6:4, weighing Compolyamonia-PVA according to a mass ratio of Compolyamonia-PVA / (PLA+PPC-P)=5:95, then adding the degradable matrix raw material and Compolyamonia-PVA simultaneously into an appropriate amount of dimethyl sulfoxide solvent, stirring and dissolving at room temperature, preparing a spinning solution with a mass concentration of the degradable matrix raw material of 5wt%, and then filtering and standing for degassing;

[0120] (2) Turn on the electrospinning machine and set the spinning conditions: spinning voltage 40 kV, solution flow rate 1 mL / h, collection roller speed 800 rpm, and a distance of 15 cm between the collection roller and the electrode; first cover the collection roller with a collection substrate layer, then start the collection roller, then start the spinning solution pump switch, and finally connect the high voltage power supply to the spinning electrode to start spinning;

[0121] (3) When the spinning time reaches 45 minutes, turn off the spinning solution delivery pump, the collecting roller, and the spinning power supply, and then peel off the micro-nano fiber membrane from the collecting roller substrate layer.

[0122] Embodiment 14

[0123] A micro-nano fiber membrane is prepared by the following steps:

[0124] (1) weighing a degradable matrix raw material according to a mass ratio of PLA / PPC-P=6:4, weighing Compolyamonia-PVA according to a mass ratio of Compolyamonia-PVA / (PLA+PPC-P)=5:95, then adding the degradable matrix raw material and Compolyamonia-PVA simultaneously into an appropriate amount of dimethyl sulfoxide solvent, stirring and dissolving at room temperature, preparing a spinning solution with a mass concentration of the degradable matrix raw material of 5wt%, and then filtering and standing for degassing;

[0125] (2) Turn on the electrospinning machine and set the spinning conditions: spinning voltage 30 kV, solution flow rate 1 mL / h, collection roller speed 800 rpm, and a distance of 10 cm between the collection roller and the electrode; first cover the collection roller with a collection substrate layer, then start the collection roller, then start the spinning solution pump switch, and finally connect the high voltage power supply to the spinning electrode to start spinning;

[0126] (3) When the spinning time reaches 45 minutes, turn off the spinning solution delivery pump, the collecting roller, and the spinning power supply, and then peel off the micro-nano fiber membrane from the collecting roller substrate layer.

[0127] Embodiment 15

[0128] A micro-nano fiber membrane is prepared by the following steps:

[0129] (1) weighing a degradable matrix raw material according to a mass ratio of PLA / PPC-P=6:4, weighing Compolyamonia-PVA according to a mass ratio of Compolyamonia-PVA / (PLA+PPC-P)=5:95, then adding the degradable matrix raw material and Compolyamonia-PVA simultaneously into an appropriate amount of dimethyl sulfoxide solvent, stirring and dissolving at room temperature, preparing a spinning solution with a mass concentration of the degradable matrix raw material of 5wt%, and then filtering and standing for degassing;

[0130] (2) Turn on the electrospinning machine and set the spinning conditions: spinning voltage 30 kV, solution flow rate 1 mL / h, collection roller speed 800 rpm, and a distance of 20 cm between the collection roller and the electrode; first cover the collection roller with a collection substrate layer, then start the collection roller, then start the spinning solution pump switch, and finally connect the high voltage power supply to the spinning electrode to start spinning;

[0131] (3) When the spinning time reaches 45 minutes, turn off the spinning solution delivery pump, the collecting roller, and the spinning power supply, and then peel off the micro-nano fiber membrane from the collecting roller substrate layer.

[0132] Example 16

[0133] (1) weighing the biodegradable matrix raw material according to the mass ratio of PLA / PPC-P=6:4, weighing Compolyamonia-PVA according to the mass ratio of Compolyamonia-PVA / (PLA+PPC-P)=5:95, then turning on the power of the micro extruder, and setting the extrusion parameters: 50°C in zone 1, 160°C in zone 2, 170°C in zone 3, 190°C in zone 4, and 185°C in zone 5;

[0134] (2) Turn on the electrospinning unit and set the spinning conditions: spinning voltage 40 kV, after the melt is stably output, set the screw speed to 2 rpm, the collecting roller speed to 1200 rpm, and the distance between the spinneret and the electrode plate to 15 cm;

[0135] (3) After the micro extruder is preheated to the set temperature and stabilized, the biodegradable matrix raw material and Compolyamonia-PVA are premixed and added to the hopper of the micro extruder; first, a collecting substrate layer is covered on the collecting roller, then the collecting roller is started, and then the micro extruder screw is started, and the spinning unit electrode switch is turned on to start spinning;

[0136] (4) After the spinning is stable, the product is collected. When the spinning time reaches 45 minutes, the micro extruder, the collecting roller, and the spinning unit power are turned off, and then the micro-nano fiber membrane is peeled off from the collecting roller substrate layer.

[0137] Comparative Example 1

[0138] A micro-nano fiber membrane is prepared by the following steps:

[0139] (1) weighing a degradable matrix raw material according to a mass ratio of PLA / PPC-P=6:4, then adding the degradable matrix raw material into an appropriate amount of dimethyl sulfoxide solvent, stirring and dissolving at room temperature to prepare a spinning solution with a mass concentration of the degradable matrix raw material of 5wt%, and then filtering and standing for degassing;

[0140] (2) Turn on the electrospinning machine and set the spinning conditions: spinning voltage 30 kV, solution flow rate 1 mL / h, collection roller speed 800 rpm, and a distance of 15 cm between the collection roller and the electrode; first cover the collection roller with a collection substrate layer, then start the collection roller, then start the spinning solution pump switch, and finally connect the high voltage power supply to the spinning electrode to start spinning;

[0141] (3) When the spinning time reaches 45 minutes, turn off the spinning solution delivery pump, the collecting roller, and the spinning power supply, and then peel off the micro-nano fiber membrane from the collecting roller substrate layer.

[0142] Comparative Example 2

[0143] A micro-nano fiber membrane is prepared by the following steps:

[0144] (1) weighing the degradable matrix raw material according to the mass ratio of PLA / PPC-P=6:4, weighing Compolyamonia according to the mass ratio of Compolyamonia / (PLA+PPC-P)=5:95, then adding the degradable matrix raw material and Compolyamonia into an appropriate amount of dimethyl sulfoxide solvent at the same time, stirring and dissolving at room temperature, preparing a spinning solution with a mass concentration of the degradable matrix raw material of 5wt%, and then filtering and standing for degassing;

[0145] (2) Turn on the electrospinning machine and set the spinning conditions: spinning voltage 30 kV, solution flow rate 1 mL / h, collection roller speed 800 rpm, and a distance of 15 cm between the collection roller and the electrode; first cover the collection roller with a collection substrate layer, then start the collection roller, then start the spinning solution pump switch, and finally connect the high voltage power supply to the spinning electrode to start spinning;

[0146] (3) When the spinning time reaches 45 minutes, turn off the spinning solution delivery pump, the collecting roller, and the spinning power supply, and then peel off the micro-nano fiber membrane from the collecting roller substrate layer.

[0147] Appearance and morphology characterization of micro-nanofiber membranes

[0148] The actual picture of the micro-nano fiber membrane prepared in Example 5 is as follows Figure 1 As shown, the white part is the micro-nano fiber membrane sample, and the other colors are the background of the photo; the micro-nano fiber membrane prepared in Example 5 was subjected to scanning electron microscopy analysis, and the fibers on the surface of the micro-nano fiber membrane were taken with conductive adhesive, and then observed by scanning electron microscopy. The morphology of the micro-nano fibers is as follows Figure 2 As shown (where a and b use different resolutions).

[0149] Micro-nano fiber membrane performance test

[0150] The micro-nano fiber membrane samples prepared in the examples and comparative examples, as well as the commercially available antibacterial meltblown nonwoven fabric (from SD LAB KOREA Inc., South Korea, product model SD-Pro), were subjected to various performance tests. The following are the reference standards for various performance test methods:

[0151] 1. Gram weight test: The gram weight measurement of fiber materials refers to "GB / T 24218.1-2009 Textiles - Test methods for nonwoven fabrics - Part 1: Determination of mass per unit area".

[0152] 2. Fiber film thickness test: Use an electronic thickness gauge to directly measure at 25°C and 65% relative humidity, accurate to microns.

[0153] 3. Fiber average diameter test: The test of the average fiber diameter in fiber materials refers to "GB / T 36422-2018 Determination of chemical fiber micromorphology and diameter by scanning electron microscopy".

[0154] 4. Air permeability test: The air permeability test of fiber materials refers to "GB / T 24218.15-2018 Textiles - Test methods for nonwoven fabrics - Part 15: Determination of air permeability".

[0155] 5. Filtration efficiency test: The filtration efficiency test of fiber materials shall be tested in accordance with Section 5.5 of GB 19083-2023 Medical Protective Masks.

[0156] 6. Dissolution test: Cut the fiber membrane sample into 3cm×3cm samples with a cutter as the test sample, and each sample is paralleled 3 times. Before the test begins, first use an electronic analytical balance to weigh the weight of the test sample that has been dried to a constant weight, record it as L0, then clamp the dried test sample with clean stainless steel tweezers and soak it in a room temperature alcohol-water mixed solvent of about 25°C (add 6 volumes of deionized water to 4 volumes of anhydrous ethanol). During the soaking process, ensure that the sample is always below the liquid level, and stop soaking when the sample is soaked at room temperature for 72 hours. After the soaking is completed, use stainless steel tweezers to remove the sample from the solvent, wait for the solvent on the surface of the sample to drip clean, then place the sample in a 100°C oven to dry to a constant weight, and then use an electronic analytical balance to weigh its weight after soaking and drying, record it as L1, and the sample dissolution rate calculation formula is: water dissolution rate (%) = (L0-L1) / L0×100%.

[0157] 7. Antibacterial performance test: The antibacterial performance test of fiber materials refers to "GB / T 20944.1-2007 Evaluation of antibacterial properties of textiles Part 1: Agar plate diffusion method" (i.e. inhibition zone method, the diffusion method is more intuitive to observe the effect) and "GB / T20944.3-2008 Evaluation of antibacterial properties of textiles Part 3: Oscillation method" (the oscillation method is convenient for quantifying antibacterial efficiency).

[0158] The test results of 1-6 above are shown in Table 1.

[0159] Table 1

[0160]

[0161]

[0162] It can be seen from the test results in Table 1 that the micro-nano fiber membrane of the present invention is thinner than the traditional commercially available antibacterial melt-blown non-woven fabric, the fiber diameter is finer, the air permeability is better, and the filtration efficiency is also very high, there is no dissolution, and it is safer for users; and the commercially available antibacterial melt-blown non-woven fabrics use organic small molecules or inorganic metal particles, and there is a certain degree of dissolution. The dissolution rate of the embodiment of the present invention is lower than that of the comparative example 2, indicating that the composite antibacterial agent of the present invention has better compatibility and stability in the degradable matrix material. Therefore, the composite antibacterial agent of the present invention will be more durable and stable in the fiber material, and the long-term protection effect will be better.

[0163] It can be seen from the results of Examples 1-15 that the spinning process conditions have a certain influence on the diameter and gram weight of the fiber. Generally, the higher the mass concentration of the spinning solution, the larger the diameter of the fiber will be, and the same spinning time will increase the gram weight of the fiber membrane; the higher the spinning voltage, the thinner the fiber diameter will be.

[0164] Test of antibacterial properties: Micro-nano fiber membrane samples with different composite antibacterial agent contents were prepared by using different mass ratios of Compolyamonia-PVA / (PLA+PPC-P), namely, Compolyamonia-PVA / (PLA+PPC-P)=2.5:97.5 (Example 6), 5:95 (Example 1), 7.5:92.5 (Example 7), and 10:90 (Example 8), and the antibacterial properties were tested by the plate diffusion method, i.e., the inhibition zone test method. The test results are shown in FIG. Figure 3 shown.

[0165] exist Figure 3 In the figure, from top to bottom, there are three groups of tests for Staphylococcus aureus, Escherichia coli, and Candida albicans. The numbers on the samples correspond to the samples prepared in the above embodiments with different mass ratios, specifically, the samples prepared in Embodiment 6 (numbered 1), Embodiment 1 (numbered 2), Embodiment 7 (numbered 3), and Embodiment 8 (numbered 4); Figure 3 It can be seen intuitively that the antibacterial performance increases with the increase of the content of the composite antibacterial agent.

[0166] In addition, the micro-nano fiber membrane material is sandwiched between two layers of spunbond non-woven fabrics to form a composite SMS structure (instead of traditional meltblown non-woven fabrics), and then made into disposable flat mask samples. The antibacterial properties are measured after the user wears it continuously for 24 hours and 72 hours (including 72 hours and 168 hours) (the wearing time is not less than 8 hours per day). Specifically, the oscillation method is used for testing: different micro-nano fiber membrane samples of the same mass are soaked and shaken with physiological saline, and then a certain amount of the shaking soaking liquid is taken as the source of bacteria, and the culture solution is added for the same time of culture, and then the antibacterial effect is observed and counted. The test results are shown in Table 2 and Figure 4 shown.

[0167] Table 2

[0168]

[0169] It can be seen from the test results of Table 2 that the embodiments of the present invention (except Example 6) have better long-term antibacterial effect than commercially available antibacterial meltblown nonwovens, and the antibacterial effect retention rate after 72 hours of use is higher and the lasting effect is stronger. In the embodiment of the present invention, as the content of the composite antibacterial agent in the fiber membrane material increases, its antibacterial efficiency gradually increases, and when the mass ratio of Compolyamonia-PVA / (PLA+PPC-P) is ≥5:95, it has a higher lasting antibacterial effect. However, the fiber membrane prepared by Comparative Example 1 without adding an antibacterial agent and Example 6 when the mass ratio of Compolyamonia-PVA / (PLA+PPC-P) is 2.5:97.5, the antibacterial rate and persistence are both low, and its use value is also low.

[0170] Figure 4 This is a comparison chart of the antibacterial properties of mask samples made using the micro-nano fiber membrane material of Example 5 of the present invention and a commercially available antibacterial melt-blown non-woven fabric after use for different periods of time; the test bacteria is Staphylococcus aureus.

[0171] exist Figure 4 In the figure, a is the mask sample of Example 5 used for 24 hours, b is the mask sample of Example 5 used for 72 hours; c is the mask sample of commercially available antibacterial melt-blown non-woven fabric used for 24 hours, d is the mask sample of commercially available antibacterial melt-blown non-woven fabric used for 72 hours; Figure 4 It can also be seen intuitively that under the same test conditions, the micro-nano fiber membrane material of Example 5 of the present invention has better long-term antibacterial efficiency and stability than the commercially available antibacterial meltblown non-woven fabric.

[0172] The preferred embodiments of the present invention are specifically described above, but the invention is not limited to the embodiments. Those skilled in the art may make various equivalent modifications or substitutions without violating the spirit of the invention. These equivalent modifications or substitutions are all included in the scope defined by the claims of this application.

Claims

1. A micro-nano fiber material, characterized in that: The raw materials for preparing the micro-nano fiber material include a degradable matrix and a composite antibacterial agent. The raw materials for preparing the composite antibacterial agent include polyvinyl alcohol and a polymer antibacterial agent. The polymer antibacterial agent is a ternary copolymer quaternary ammonium salt polymer antibacterial agent disclosed in CN117304390A.

2. The micro-nano fiber material according to claim 1, characterized in that: The mass ratio of the degradable matrix to the composite antibacterial agent is 98:2 to 50:

50.

3. The micro-nano fiber material according to claim 1, characterized in that: The degradable matrix includes at least one of polylactic acid, polyvinyl alcohol, polycaprolactone, polybutylene succinate, polybutylene terephthalate and polybutylene adipate copolymer, polypropylene carbonate, polyester-polypropylene carbonate copolymer, polyhydroxyalkanoate, lignin, plant cellulose, cotton, linen, and silk.

4. The micro-nano fiber material according to claim 1, characterized in that: The alcoholysis degree of the polyvinyl alcohol is 30% to 95%; and / or the number average molecular weight of the polyvinyl alcohol is 5000 to 120000; and / or the molecular weight distribution width of the polyvinyl alcohol is 2 to 4; and / or the average polymerization degree of the polyvinyl alcohol is 100 to 2500.

5. The micro-nano fiber material according to claim 1, characterized in that: The number average molecular weight of the polymer antibacterial agent is 2000 to 100000; and / or, the molecular weight distribution width of the polymer antibacterial agent is 1 to 4; and / or, in the molecular main chain of the polymer antibacterial agent, the molar ratio of N,N-dimethyl-N-allyl dodecyl ammonium bromide to vinyl tri(methoxy)silane is 3:7 to 9:

1.

6. The micro-nano fiber material according to claim 1, characterized in that: The mass ratio of the polymer antibacterial agent to polyvinyl alcohol is 10:0.1 to 1:

9.

7. The method for preparing the micro-nano fiber material according to any one of claims 1 to 6, characterized in that: The following steps are involved: The polyvinyl alcohol and the high molecular weight antibacterial agent are mixed and cross-linked to obtain the composite antibacterial agent; The degradable matrix and the composite antibacterial agent are mixed and spun to obtain the micro-nano fiber material.

8. The preparation method according to claim 7, characterized in that: The temperature of the cross-linking reaction is 70 to 200° C.; and / or the time of the cross-linking reaction is 60 seconds to 10 hours.

9. The preparation method according to claim 7, characterized in that: The spinning adopts one of melt-blowing spinning, melt electrostatic spinning or solution electrostatic spinning.

10. The use of the micro-nano fiber material according to any one of claims 1 to 6, characterized in that: The application includes the use of the micro-nano fiber material in the preparation of disposable sanitary products, disposable protective products, Band-Aids, medical bandages, and filtration and purification products.

Citation Information

Patent Citations

  • Ternary copolymerized quaternary ammonium salt macromolecular antibacterial agent as well as preparation method and application thereof

    CN117304390A